Laparoscopic cholecystectomy in infected pancreatic necrosis in the era of “step up approach” - Ayon, Carlos; Orduna, Gabriel; Pezzutti, Hernán; Tedesco, Juan; Martínez, Federico; Rotryng, Ariel (Revista Argentina de Cirugía, 2021)
Background: the “step up” approach is a valid therapeutic option for the treatment of infected necrotizing pancreatitis. However, the time and type of treatment of the underlying biliary condition is a controversial issue. Objectives: to assess the feasibility and opportunity of the laparoscopic treatment of the underlying biliary pathology after the “step up” approach for the necrotizing pancreatitis. Setting: Hospital Interzonal General de Agudos Dr Luis Güemes, Haedo, Provincia de Buenos Aires, Argentina. Methods: data collected from 13 patients with necrotizing pancreatitis who were treated by a “step up” approach and then operated by laparoscopic technique are described. Inclusion and exclusion criteria, opportunity and type of treatment, as well as mean operation time, grade of difficulty, con- version, morbidity and mortality rates are analyzed. Results: laparoscopic cholecystectomy was undertaken in all of patients. The mean time from the start of the “step up” approach to laparoscopic cholecystectomy was 67 days. Laparoscopic exploration and stone extraction by transcystic approach were necessary in two patients (15,38%). Mean operation time was 97 minutes and no major technical difficulties were described in accordance with a specific score adopted. No conversions, nor morbidity or mortality were observed in this series. Conclusions: laparoscopic treatment after the “step up” approach for necrotizing pancreatitis was a feasible and safe option for the definitive treatment of biliary calculous pathology in this group of patients.